Analisis Hermeneutika Asma Barlas terhadap Ayat Qawwamun dan Nusyuz dalam QS. An-Nisa’: 34-35 dan 128 - Healthy Habitue; Nurhasanah; Muhammad Fajri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This research is intended to examine the interpretation of Qur’anic verses concerning qawwamun and nusyuz in Q.S. an-Nisa’ (4): 34–35 and 128 through the lens of Asma Barlas’ hermeneutical framework. The study adopts a qualitative design in the form of library research, drawing on primary sources such as the Qur’an and Barlas’ writings, alongside supporting references from both classical and contemporary tafsir. Data collection is carried out through a documentation technique, while the analysis employs a descriptive-analytical approach that involves thematic mapping, examination of key linguistic elements, intertextual analysis, exploration of historical context, and a critical reassessment of interpretations influenced by patriarchal perspectives. The results reveal that the Qur’anic discourse on gender relations fundamentally promotes principles of justice, mutuality, and ethical accountability, rather than legitimizing hierarchical authority. Within this framework, Barlas reinterprets qawwamun as a notion of responsibility instead of dominance, and understands nusyuz as a form of relational imbalance that can arise from either spouse. In sum, the study underscores that gender inequality in Muslim contexts is more closely tied to interpretive traditions than to the Qur’anic text itself, thereby affirming the need for contextual and critical reinterpretation to foster a more equitable and balanced understanding. This article contributes to contemporary Qur’anic studies by offering a critical engagement with patriarchal readings of gender-related verses through a hermeneutical approach grounded in tawhidic principles and textual contextualization. It also enriches the discourse of Islamic gender studies by demonstrating how reinterpretation of qawwamun and nusyuz can support more egalitarian and dialogical marital relations within Muslim societies